Entangled Communities: Religion and Ethnicity in Ontario and North America, 1880–1930 - Bryce, Benjamin (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2012)
This article examines the relationship between religion, ethnicity, and space in Ontario between 1880 and 1930. It tracks the spread of organized Lutheranism across Ontario as well as the connections that bound German-language Lutheran congregations to the United States and Germany. In so doing, this article seeks to push the study of religion in Canada beyond national boundaries. Building on a number of studies of the international influences on other denominations in Canada, this article charts out an entangled history that does not line up with the evolution of other churches. It offers new insights about the relationship between language and denomination in Ontario society, the rise of a theologically-mainstream Protestant church, and the role of institutional networks that connected people across a large space. The author argues that regional, national, and transnational connections shaped the development of many local German-language Lutheran communities in Ontario.